Strategic household behavior in labor surplus economies - Fabella, Raul V. (1991)
We show that when households employ the Cournot-Nash strategy in labor surplus economies, the wage rate is strictly positive, households are underemployed, household members may be openly unemployed, the labor supply curve is upward-sloping and household withdrawal but not worker withdrawal decreases output.
Includes bibliographical references (page 126).
Keywords: Households -- Economic aspects; Wages; Labor market